(untitled) (Research, Society and Development, 2021)
The city of Macapá is undergoing a process of territorial expansion, namely: the creation of new neighborhoods without any planning coming from organs municipal. Therefore, the afforestation of streets and public sidewalks is responsible for the residents, who often select inappropriate trees. Thus, it is essential to determine the diversity and composition of tree species, and their relationships with hemiparasites in urban afforestation. The objective of this work was to evaluate and identify the relationships of public facilities with urban afforestation, sidewalk conditions and physical space for trees, electrical wiring, among other characteristics in Macapá. The inventory of tree species and hemiparasites was determined in tree individuals with ≥ 5cm in diameter at breast height (DBH) and ≥1.3 m in height present in the afforestation of public streets and public ride in three neighborhoods (Jesus de Nazaré, Centro and Santa Inês). Afterwards, they were identified with the help of specialized literature, comparison with materials deposited at the Herbarium Amapaense (HAMAB) and consultations in online herbariums. Analysis of the relationship between afforestation and public facilities and Jaccard’s similarity index. A total of 3434 individuals were found in the urban afforestation of Macapá, with a greater predominance of the species Mangífera indica L. and the family with the largest number of individuals was Anacardiaceae. Jaccard’s similarity showed that the Jesus de Nazaré and Santa Inês neighborhoods showed similarity in the number of infested individuals per family and with the increase in the similarity index, they showed similarity with the Central neighborhood.